The Effectiveness of Constructivist Strategies in Enhancing the Speaking Skills of Students at Al-Kamal Kunir Integrated Islamic Boarding School, Blitar, and Darul Hikmah Modern Boarding School - Muhammad Syahrul Munir; Bakri Muhammad Bakheet; Miftahul Huda; Muhammad A'inul Haq; Mohammad Shohibul Anwar (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2026)
This study aims to analyze the effectiveness of constructivist strategies in enhancing the speaking skills of students at Al-Kamal Kunir Integrated Islamic Boarding School, Blitar, and Darul Hikmah Modern Boarding School, Tulungagung. The study employed a quantitative approach with an experimental method. The research design used was a quasi-experimental design with a pretest–posttest model. The subjects of the study were intermediate-level students divided into experimental and control groups. Data were collected through questionnaires, observations, and documentation. The obtained data were analyzed using descriptive and inferential statistical tests, including normality tests, homogeneity tests, and t-tests to determine differences in the improvement of speaking skills before and after the implementation of constructivist strategies. The results indicate that the application of constructivist learning strategies significantly impacts the enhancement of students’ speaking skills. This is demonstrated by differences in the mean scores of speaking skills between the experimental and control groups, as well as higher posttest scores compared to pretest scores. Constructivist strategies encourage students to be more active, confident, and directly engaged in the speaking learning process through experience, interaction, and discussion. Therefore, constructivist learning strategies are effective for improving students’ speaking skills in the boarding school context.